2001
DOI: 10.1016/s1010-7940(01)00717-5
|View full text |Cite
|
Sign up to set email alerts
|

Repair of truncus arteriosus: a considered approach to right ventricular outflow tract reconstruction

Abstract: In truncus arteriosus repair, RV to PA continuity established by a direct anastomosis was associated with a low incidence of surgical RVOT re-intervention. This technique has the potential for RVOT growth and may be a useful alternative when an appropriate allograft is unavailable, particularly in the neonate where the risk of pulmonary hypertension are lower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
67
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 18 publications
6
67
1
Order By: Relevance
“…Since McGoon et al reported the first successful surgical repair of PTA using an aortic homograft in 1967, 2 incremental advances in surgical and perioperative management have resulted in a dramatic improvement in the outcome of this entity. [3][4][5][6][7][8] However, the overall outcome in patients with PTA is till compromised by associated anomalies, such as truncal valve insufficiency 9 or interrupted aortic arch, 10 and progressive obstruction of the conduit placed in the right ventricular outflow tract (RVOT) and associated peripheral pulmonary artery (PA) stenosis. [5][6][7]11 RVOT reconstruction in patients with PTA was initially achieved using a xenograft valved synthetic conduit in the 1980s, 11 and small homografts have become the first choice with the recognition of the advantages of elective neonatal repair of this lesion, especially in North American institutes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Since McGoon et al reported the first successful surgical repair of PTA using an aortic homograft in 1967, 2 incremental advances in surgical and perioperative management have resulted in a dramatic improvement in the outcome of this entity. [3][4][5][6][7][8] However, the overall outcome in patients with PTA is till compromised by associated anomalies, such as truncal valve insufficiency 9 or interrupted aortic arch, 10 and progressive obstruction of the conduit placed in the right ventricular outflow tract (RVOT) and associated peripheral pulmonary artery (PA) stenosis. [5][6][7]11 RVOT reconstruction in patients with PTA was initially achieved using a xenograft valved synthetic conduit in the 1980s, 11 and small homografts have become the first choice with the recognition of the advantages of elective neonatal repair of this lesion, especially in North American institutes.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] However, the overall outcome in patients with PTA is till compromised by associated anomalies, such as truncal valve insufficiency 9 or interrupted aortic arch, 10 and progressive obstruction of the conduit placed in the right ventricular outflow tract (RVOT) and associated peripheral pulmonary artery (PA) stenosis. [5][6][7]11 RVOT reconstruction in patients with PTA was initially achieved using a xenograft valved synthetic conduit in the 1980s, 11 and small homografts have become the first choice with the recognition of the advantages of elective neonatal repair of this lesion, especially in North American institutes. 3,4 Nonetheless, controversy still remains over the best method of RVOT reconstruction because of the considerably high rates of re-operation on RVOT conduits, regardless of conduit type, and less availability of small homografts in many countries, including Japan.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative surgical options are taken in consideration, like the use of a non-valved conduit implantation to delay the conduit failure due to progressive stenosis and dysfunction of the conduit valve (65)(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…The data available in the literature show that, on a midterm basis, the use of non valved conduit may decrease the need for re-operation for right ventricular outflow tract stenosis and may promote an adequate growth of the pulmonary arteries in selected congenital heart defects, like truncus arteriosus (65)(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%